Biochemical Roles of Eukaryotic Cell Surface Macromolecules 2011 ISCSM Proceedings - Sudhakaran, Perumana R.; Surolia, Avadhesha (Springer New York : Imprint: Springer, 2012)
The 2011 international symposium on the "Biochemical Role of Eukaryotic Cell surface Macromolecules" (Trivandrum, India - Jan 2011) covered topics on the analysis of glycome, biophysical approaches to study cell surface molecules, glycoconjugate metabolism and its dysregulation, and molecular mechanisms involved in cell-cell and cell-matrix interaction.  Contributions from this meeting are presented this volume, providing an in-depth analysis of data on cell surface macromolecules in cellular function and their alteration associated with pathological conditions. All contributions are either comprehensive critical reviews or original research papers and cover the most relevant and recent topics related to functional role of cell surface molecules.